A Cross-Species Systems Genetics Analysis Links APBB1IP as a Candidate for Schizophrenia and Prepulse Inhibition - Ashbrook, David G.; Cahill, Stephanie; Hager, Reinmar (Frontiers in Behavioral Neuroscience, 2019)
Background: Prepulse inhibition (PPI) of the startle response is a highly conserved form of sensorimotor gating, disruption of which is found in schizophrenia patients and their unaffected first degree relatives. PPI can be measured in many species, and shows considerable phenotypic variation between and within rodent models. This makes PPI a useful endophenotype. Genome-wide association studies (GWAS) have been carried out to identify genetic variants underlying schizophrenia, and these suggest that schizophrenia is highly polygenic. GWAS have been unable to account for the high heritability of schizophrenia seen in family studies, partly because of the low power of GWAS due to multiple comparisons. By contrast, complementary mouse model linkage studies often have high statistical power to detect variants for behavioural traits but lower resolution, producing loci that include tens or hundreds of genes. To capitalise on the advantages of both GWAS and genetic mouse models, our study uses a cross-species approach to identify novel genes associated with PPI regulation, which thus may contribute to the PPI deficits seen in schizophrenia. Results: Using experimental data from the recombinant inbred mouse panel BXD, we identified two significant loci affecting PPI. These genomic regions contain genetic variants which influence PPI in mice, and are therefore candidates that may be influencing aspects of schizophrenia in humans. We next investigated these regions in whole genome data from the Psychiatric Genomics Consortium schizophrenia GWAS and identify one novel candidate gene (ABPP1IP) that was significantly associated with PPI in mice and risk of schizophrenia in humans. A systems genetics approach demonstrates that APBB1IP coexpresses with several other genes related to schizophrenia in several brain regions. Gene coexpression and enrichment analysis shows clear links between APBB1IP and the immune system. Conclusion: The combination of human GWAS and mouse QTL from some of the largest study systems available has enabled us to identify a novel gene, APBB1IP, which influences schizophrenia in humans and PPI in mice.